Depressive Realism Hypothesis: Reflections and Critical Analysis - Dilwar Hussain, Dilwar Hussain (International Journal of Psychosocial Rehabilitation, 2013)
This paper is an attempt to critically analyze depressive realism hypothesis, which states that depressed people are more ac- curate in their perceptions and judgments than their non-depressed counterparts. Studies using diverse research methods supporting depressive realism are reviewed. Possible mechanisms that may explain depressive realism such as self-focused attention and self-schemas are discussed. Finally, conceptual and methodological issues pertaining to depressive realism are addressed for future research.